A mechano- and thermoresponsive luminescent cyclophane. Issue 33 (4th April 2016) - Sagara, Yoshimitsu; Simon, Yoan C.; Tamaoki, Nobuyuki; Weder, Christoph
Abstract : The first mechano- and thermoresponsive luminescent cyclophane is described in this report. Abstract : The first fluorescent cyclophane with mechano- and thermoresponsive solid-state fluorescence characteristics is reported. The new cyclophane comprises two 9, 10-bis(phenylethynyl)anthracene moieties that are bridged by tetraethylene glycol spacers. The stimuli-responsiveness is based on molecular assembly changes.